Fibrilasi Atrial pada sindrom WPW - Dony Yugo; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2014)
Background : In large-scale general population studies involving children and adults, the prevalence of WPW is estimated to be 1–3 in 1000 individuals. At present, it is estimated that approximately 65% of adolescents and 40% of individuals over 30 years with WPW pattern on a resting ECG are asymptomatic. An incidence of 4.5 episodes of sudden death, including resuscitated sudden cardiac death (SCD), per 1000 patient-years was recently reported. The mechanism of sudden cardiac death in patients with WPW is thought to be associated with atrial fibrillationCase Illustration : We reported a case of 45 year old female came with unstable irregular wide complex tachycardia in the form of pre-excited AF. Cardioversion successfully terminate the tachyaarhythmias. ECG in sinus rhythm revealed WPW pattern ECG. Patient then referred for catheter ablation. Successful ablation was done resulting a normal pattern ECGConclusion : AF in WPW syndrome could lead to devastating events such as cardiac arrest. ECG recognition at the first place is very important for early management. Early stratification and management in patients with WPW is important to diminished the risk of AF occurence and SCD.